Movement and Song as a Multisensory Strategy to Enhance Hadith Memorization in Early Childhood - Pusparini, Dewi; Musayyadah, Musayyadah; Ismaiyah , Nurul; Fitriyah, Nurul (JURNAL PENDIDIKAN USIA DINI, 2026)
Hadith memorization in early childhood education is still largely dominated by repetitive and teacher-centered instructional practices that limit children’s engagement and holistic learning development. Although previous studies have reported positive effects of movement-based or song-based strategies, most investigations have examined these approaches separately. Empirical evidence that integrates movement and song as a unified multisensory instructional strategy in early childhood hadith learning remains limited, indicating the need for further investigation. This study aims to examine the effectiveness of integrating movement and song as a multisensory strategy in enhancing early childhood hadith memorization across cognitive, affective, and psychomotor domains. A Classroom Action Research design was employed involving 22 children aged 4–5 years and conducted over two instructional cycles. The learning intervention integrated simple body movements and rhythmic songs aligned with the meaning and sequence of selected short hadiths. Data were collected through structured observation sheets assessing memorization accuracy, learning engagement, and movement coordination, and analyzed using percentage-based achievement indicators supported by descriptive qualitative analysis. The results indicate consistent improvement across all domains. Cognitive achievement increased from 23% to 77%, affective engagement improved from 68% to 86%, and psychomotor performance increased from 64% to 82%. The novelty of this study lies in its empirical evidence that the integration of movement and song functions as a coherent multisensory pedagogical framework rather than as separate instructional techniques, offering a developmentally appropriate alternative to conventional rote memorization practices in early childhood Islamic education.